2017
DOI: 10.1177/0394632017742505
|View full text |Cite
|
Sign up to set email alerts
|

Local pro-inflammatory cytokine and nitric oxide responses are elevated in patients with pterygium

Abstract: Pterygium is a common ocular surface disease observed in humans. Chronic ultraviolet (UV) exposure is extensively recognized as an aetiological factor in the pathogenesis of this disease. This hypothesis is sustained by epidemiological and histopathological data in relation to UV injured skin. Although some findings have indicated that genetic factors, anti-apoptotic and immunological mechanisms are involved in the pathogenesis of pterygium, the mechanism by which it develops remains poorly understood. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 43 publications
(80 reference statements)
1
11
0
Order By: Relevance
“…In addition, IL-6 and other UVB-associated proinflammatory secretions contribute to the infiltration of different immune cells that produce proangiogenic factors [35, 36]. Further substantiating our hypothesis of an enhanced tear film cytokine production are the increased IL-6 levels found in reflex tears of pterygium patients [37]. However, to our knowledge, no report has yet been published regarding the course of these proinflammatory cytokine levels after surgical intervention and into the recovery period post pterygiectomy.…”
Section: Introductionsupporting
confidence: 63%
“…In addition, IL-6 and other UVB-associated proinflammatory secretions contribute to the infiltration of different immune cells that produce proangiogenic factors [35, 36]. Further substantiating our hypothesis of an enhanced tear film cytokine production are the increased IL-6 levels found in reflex tears of pterygium patients [37]. However, to our knowledge, no report has yet been published regarding the course of these proinflammatory cytokine levels after surgical intervention and into the recovery period post pterygiectomy.…”
Section: Introductionsupporting
confidence: 63%
“…Various studies have shown that LPS stimulation induces the secretion of various proinflammatory mediators, such as NO and ROS [24, 25]. The production and secretion of NO can induce local tissue damage and further trigger inflammation [26]. Therefore, the inhibition of NO production is an important therapeutic strategy for the treatment of inflammatory diseases [27].…”
Section: Discussionmentioning
confidence: 99%
“…Given the nature of pterygium lesions, even when it is symptomatic, it usually generates at most irritation, itching or burning sensation, tearing, red eye or foreign body sensation, determining a mild eye pain [18][19]. Zidi et al have demonstrated that the clinical redness is significantly correlated with the chronic inflammatory response (P < 0.001) [1]. Signs of blurred vision appear when the lesion is significantly grown and it partially covers the cornea [20], obscuring the visual axis, or it may determine astigmatism [15].…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, there are no similar studies, based on lesion sizes measured before surgery and associated symptoms, in order to correlate our findings. Zidi et al have searched for a connection between the extent of pterygium lesions and the chronic inflammatory response, identifying a reverse correlation between those two parameters, but did not perform a comparison between males and females [1]. In fact, UV light, which is one of the main factors in pterygium formation [21], induces a series of chronic inflammation cells within the conjunctiva.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation